Enhancing the antibacterial activity of Lactobacillus reuteri against Escherichia coli by random mutagenesis and delineating its mechanism. (February 2023) - Ma, Enyun; An, Yingfeng; Zhang, Guoyan; Zhao, Mei; Iqbal, Muhammad Waheed; Zabed, Hossain M.; Qi, Xianghui
Abstract: In this study, Limsolactobacillus reuteri was genetically modified through random mutagenesis with atmospheric and room temperature plasma (ARTP), and mutants were screened for their antibacterial activity against Escherichia coli using high-throughput screening (HTS), which finally provided a mutant strain named AR-148. The cell-free supernatant of AR-148 (MCFS) exhibited 37% higher antibacterial activity on E. coli compared to the wild strain. Subsequently, the antibacterial effects of MCFS were studied at the cellular level, including membrane integrity, energy metabolism of key enzymes, DNA replication, and protein synthesis. The results revealed that MCFS exerted its antibacterial effects by disrupting cell membranes, affecting intracellular biomolecules (protein and DNA), and decreasing the contents of the intracellular enzymes (AKPase and β -galactosidase). Further transcriptome analysis confirmed that MCFS had significant effects on the expression of genes in E. coli involved in energy metabolism, oxidative stress, cell wall and cell membrane integrity, and genetic information. In this way, the present study revealed the antibacterial mechanism of MCFS against a Gram-negative bacterium for the first time, providing an experimental insight into antibacterial activity, which might be useful for further development and application of MCFS in food industries. Graphical abstract: Image 1 Highlights: L. reuteri was mutated by ARTP to enhance its antibacterial activity on E. coli. The antibacterial activity of the selected mutant (AR-148) was increased by 37%. AR-148 cell-free supernatant affected E. coli cell membrane and macromolecules. Transcriptome analysis revealed up/down-regulated genes of various pathways.